Albumin Macroaggregates Labelled with Tc99m - De Paoli, T.; Hager, A.; Nicolini, J. O.; Radicella, Renato (Northern Ireland, 1966)
Fil: Radicella, Renato Comisión Nacional de Energía Atómica; Argentina